Theoretical – experimental evaluation of capacity measures for beams of central suspension of the disel trains DR1A - Bondarev, O. M.; Yahoda, D. O.; Skoblenko, V. M. (Science and Transport Progress, 2011)
In the paper the results of experimental-and-theoretical evaluation of strength indices for central swing bolsters of diesel trains DR1A are presented and the variants of modernization and improvement of the strength indices are recommended.